2015
DOI: 10.25095/mufad.396573
|View full text |Cite
|
Sign up to set email alerts
|

Muhasebe Kârları İle Hisse Senedi Fiyatları Arasındaki İlişki: BİST Firmaları Üzerine Bir Uygulama

Abstract: Hisse senetleri yatırımcılarına sermaye kazancı ve temettü geliri sağlamaktadır. Bu nedenle firma kârları hisse senedi yatırımcılarının yatırım kararlarını ve hisse senedini fiyatını etkileyen önemli bir faktördür. Bu çalışmanın amacı, firmaların muhasebe kârları ile hisse senedi fiyatları arasındaki ilişkinin incelenmesidir. Bu amaçla, BİST Gıda, İçki ve Tütün Sektöründe faaliyet gösteren firmaların 2000-2013 yıllarında elde ettikleri muhasebe kârları ile hisse senedi fiyatları arasında ilişki panel eşbütünle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 4 publications
(4 reference statements)
1
6
0
3
Order By: Relevance
“…Akyatan (2016), Kaya and Öztürk (2015), Aktaş and Ünal (2015) and also Parlakkaya and Kahraman (2017) reached the similar results. On the other hand, Sevim (2016) revealed that there is no significant relationship between ROA, ROE ratios and stock returns.…”
Section: Research Findings and Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Akyatan (2016), Kaya and Öztürk (2015), Aktaş and Ünal (2015) and also Parlakkaya and Kahraman (2017) reached the similar results. On the other hand, Sevim (2016) revealed that there is no significant relationship between ROA, ROE ratios and stock returns.…”
Section: Research Findings and Discussionsupporting
confidence: 71%
“…On the other hand, Aydemir, Ögel and Demirtaş (2012), also Kaya and Öztürk (2015) split companies into sectors and then analyzed them. In the context of these studies, selected indexes and sectors differ in terms of the number of companies dealt with and the periods in which the study's data set was formed.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Avan, Siddique, and Sarwar (2014) carried out a study using the data obtained from 59 corporates listed in Pakistan's KSE100 index and indicated that changes in stock values were influenced by EVA and such effects were found to be significant at p < 0.1. Kaya and Öztürk (2015) carried out a study to investigate the relationships between accounting profits and stock quotes. They investigated the relationships between the accounting profits of corporates operating in the ISE Food, Beverage, and Tobacco Sectors for the 2000-2013 period and the stock quotes of these corporations.…”
Section: Literaturementioning
confidence: 99%
“…Petcharabul ve Romprasert (2014), Tayland'da 1997-2011 dönemine ilişkin çeyrek dönem mali tablo verileri ile çalışarak Teknoloji sektöründe bulunan firmaların hisse senetlerinin faaliyet sonuçları ile hisse senedi borsa getirileri arasındaki ilişkileri ölçmüşlerdir. Yazarlar, Özsermaye karlılığı ve PD/DD oranları ile hisse getirisi arasında önemli pozitif ilişki elde etmişlerdir Kaya ve Öztürk (2015),. firma kârlarının, hisse senedi yatırımcılarının yatırım kararlarını ve hisse senedini fiyatını etkileyen önemli bir faktör olduğunu ifade etmişlerdir.…”
unclassified